The persistence and spatial transformations of traditional Joglo house according to hamemayu hayuning bawana philosophy - Brigitta Michelle; Yohanes Djarot Purbadi (ARTEKS : Jurnal Teknik Arsitektur, 2021)
This research aimed to explain the conceptual persistence of spatial transformations in the Joglo house nDalem Puspodiningratan based on Hamemayu Hayuning Bawana philosophy. This philosophy is the public wisdom directed towards maintaining a harmonious relationship between humans and each other, nature, and God. This philosophy is applied in several dimensions of the Javanese life such as the architecture which is meaningfully designed. Moreover, the Hamemayu Hayuning Bawana is observed to be playing an important role in the spatial configuration of the traditional Joglo house. It is important to note that nDalem Puspodiningratan is a traditional Joglo house with a well-maintained condition and which undergoes a spatial transformation due to the inhabitation of alternating families. This research was, therefore, conducted using visual observation and documentation, literature review, interviews, graphic method, and comparison to explore the Joglo transformation data and background. The results showed the Joglo nDalem Puspodiningratan persisted in preserving the Hamemayu Hayuning Bawana's philosophical principles despite the spatial transformations. Meanwhile, the transformations discovered to be violating the traditional house rules are believed to be reducing the Hamemayu Hayuning Bawana practice while those observed to be following the rules maintain the practice. There is a need for further research on the transformations of traditional buildings in other cases of the traditional Javanese architecture to show the existence of spatial transformations and conceptual persistence related to Hamemayu Hayuning Bawana.